Faktor-faktor Penentu Indeks Pembangunan Manusia di Provinsi Jawa Barat Tahun 2016-2020 - Kumba Digdowiseiso; Novia Nur Damayanti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
This research aims to determine the effect of the regional independence ratio, capital expenditure ratio, and poverty on the Human Development Index in the Regency and City of West Java Province for the 2016 – 2020. The method of analytic was used panel data regression with used a model or Fixed Effect Modal (FEM). The level of significance in this research is 5 or 0.05. The results of this research is indicate that the regional independence ratio variable has a positive and insignificant effect on the Human Development Index variable. The capital expenditure ratio variable has a negative and insignificant effect on the Human Development Index variable. Meanwhile, the poverty variable has a negative and significant effect on The Human Development Index variable.